La calèche hippomobile : un tiers lieu éducatif ? - Chloé Mulier; Jocelyne Porcher
The horse-drawn school bus in the town of Vendargues is an exception, due to the number of children transported and the frequency of pick-ups. In this article, we hypothesize that the horse-drawn carriage is an educational "tiers-lieu" in the sense of Meirieu (2018), supported by the presence of horses, where children learn to live together. We show that this "tiers-lieu" helps to improve socialization, autonomy, but also mutual aid and responsibility between the children, in particular because of the particular framework created by the carriage. It allows children to learn to respect the rules of the community and to develop different capacities beyond the traditional educational structures of school and family. This autonomous but supervised socialization is made possible by the existence of working animals, and seems to be a new place for experiencing life together from a very early age.